ChemInform Abstract: Efficient and Convenient Synthesis, Characterization, and Antimicrobial Evaluation of Some New Tetracyclic 1, 4‐Benzothiazines. Issue 25 (June 2016) - Mor, Satbir; Nagoria, Savita
Abstract: Among the tested tetracyclic 1, 4‐benzothiazines (III), compounds (IIIg) and (IIIh) are found to be more potent than the standard drugs against A.